Atlas of Environmental Risks Facing China Under Climate Change (IHDP/Future Earth-Integrated Risk Governance Project Series,, 2018)
This atlas provides the most comprehensive and accurate overview of environmental risks relating to climate change vulnerability and adaptation in China. It addresses the agricultural, ecosystem and heat wave health risk posed by climate change and presents the projected environmental risks in the 21st century under climate change and socioeconomic scenarios. The detailed and concise risk assessments are mapped in grid units, allowing easy environmental risk assessment for specific locations. The atlas contributes significantly to the knowledge base for climate change adaptation in China and is a valuable resource for students and professionals in the fields of geographic sciences and climate change. .